Analisis Rasio CAMEL (Capital, Asset, Management, Earnings, Equity dan Liquidity) pada Tingkat Kesehatan Bank (Studi Kasus BRI Syariah Periode 2018-2019) - Andriasari, Widi Savitri; Munawaroh, Siti Ummi (BISNIS, 2020)
This study aims to determine the results of the CAMEL ratio analysis (Capital, Asset Quality, Management, Earnings and Liquidity) at the soundness level of a Sharia BRI Bank for the period 2018-2019. The soundness level of a bank is an assessment conducted by the OJK for each bank to determine whether the bank is in good health or not. Regulations regarding the assessment of the level of health at commercial banks are contained in Bank Indonesia Regulation Number 13/1/PBI/2011 and Financial Services Authority Regulation Number 8/POJK.03/2014 and Financial Services Authority Regulation Number 4/POJK.03/2016. This type of research is a descriptive study with a quantitative approach. Descriptive research method is the method used to describe the research results by analyzing data from financial statement sources. While the quantitative research method is a study that uses data in the form of numbers as a means of analyzing and calculating. For this reason, the source of data needed in this study is secondary data which is the financial statements of a Sharia BRI Bank for the period 2018-2019. Through the data source in the form of financial reports can find out the soundness level of BRI Syariah Bank in 2018-2019 by calculating and analyzing the CAMEL ratio.